2017
DOI: 10.1007/s40265-016-0682-0
|View full text |Cite
|
Sign up to set email alerts
|

Sedative Effects of Levocetirizine: A Systematic Review and Meta-Analysis of Randomized Controlled Studies

Abstract: Levocetirizine has modest sedative effects with a risk ratio of 1.67 when compared with placebo. The sedative effects observed for levocetirizine are not different from other second-generation antihistamines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 50 publications
2
10
0
2
Order By: Relevance
“…Our study demonstrates that the risk of fexofenadine on sedative effects was lower than that of the first-generation antihistamines and the second-generation antihistamines and even has been as low as placebo. A recent meta-analysis showed that levocetirizine had a mild sedative effects although it was a new generation antihistamine [69]. According to our study, fexofenadine with no sedative effect is more worthy of recommendation among the new generation antihistamines.…”
Section: Discussionsupporting
confidence: 49%
“…Our study demonstrates that the risk of fexofenadine on sedative effects was lower than that of the first-generation antihistamines and the second-generation antihistamines and even has been as low as placebo. A recent meta-analysis showed that levocetirizine had a mild sedative effects although it was a new generation antihistamine [69]. According to our study, fexofenadine with no sedative effect is more worthy of recommendation among the new generation antihistamines.…”
Section: Discussionsupporting
confidence: 49%
“…Although cetirizine produced modest sedative effects, and both levocetirizine and desloratadine produced mild sedative effects, fexofenadine had no adverse effect. These data suggest that, of the oral antihistamines available, fexofenadine is the only one that does not impair cognitive and psychomotor function, though more head-to-head trials are needed to confirm this [ 41 , 42 , 44 , 63 ]. Overall, a limited number of antihistamines are devoid of sedative effects; however, since fexofenadine displays minimal CNS infiltration, and therefore does not appear to impair cognitive and psychomotor performance, it is considered one of the few truly non-sedating antihistamines, regardless of dose [ 64 , 65 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike other H 1 receptor blockers, levocetirizine cannot penetrate the blood–brain barrier, which contributes to the weak central inhibitory effect. Although levocetirizine is well tolerated, some adverse effects were reported in patients under therapy with levocetirizine 35. Most of the adverse effects of levocetirizine were dose-dependent.…”
Section: Introductionmentioning
confidence: 99%